2008
DOI: 10.3189/172756408787814690
|View full text |Cite
|
Sign up to set email alerts
|

Snow depth derived from passive microwave remote-sensing data in China

Abstract: ABSTRACT. In this study, we report on the spatial and temporal distribution of seasonal snow depth derived from passive microwave satellite remote-sensing data (e.g. SMMR from 1978 to 1987 and SMM/I from 1987 to 2006) in China. We first modified the Chang algorithm and then validated it using meteorological observation data, considering the influences from vegetation, wet snow, precipitation, cold desert and frozen ground. Furthermore, the modified algorithm is dynamically adjusted based on the seasonal variat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
221
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 342 publications
(244 citation statements)
references
References 25 publications
4
221
0
3
Order By: Relevance
“…A complex pattern of regionally increasing and decreasing spring snow depth in the Tibetan Plateau has been observed since the 1970s (Zhang et al, 2004;Che et al, 2008;Wang et al, 2013), which could help account for the mixed MXPGR trends observed in the Tibetan Interior. Highelevation zones in the upper Indus catchment, running from the Karakorum in a southeastward direction, have seen increased precipitation over the past decades due to increases in the strength of the WWD Norris et al, 2016;Treydte et al, 2006).…”
Section: Spatial Melt Patterns From Hierarchical Clusteringmentioning
confidence: 99%
“…A complex pattern of regionally increasing and decreasing spring snow depth in the Tibetan Plateau has been observed since the 1970s (Zhang et al, 2004;Che et al, 2008;Wang et al, 2013), which could help account for the mixed MXPGR trends observed in the Tibetan Interior. Highelevation zones in the upper Indus catchment, running from the Karakorum in a southeastward direction, have seen increased precipitation over the past decades due to increases in the strength of the WWD Norris et al, 2016;Treydte et al, 2006).…”
Section: Spatial Melt Patterns From Hierarchical Clusteringmentioning
confidence: 99%
“…The snow data from the microwave remote sensors can more accurately reflect the spatial characteristics. Hence, in this study, the gridded daily snow depths derived by Che et al (2008) In this paper, the Qinghai-Tibetan Plateau is located from 74°E to 104°E and from 25°N to 40°N. Figure 1 shows the domain, topography, and regional mountain ranges in the QinghaiTibetan Plateau.…”
Section: Methodsmentioning
confidence: 99%
“…The original Chang algorithm (Chang et al,1987) for passive remote sensing of snow depth underestimates the snow depth at the beginning of the snow season and overestimates it at the end. By using SMMR and SSM/I remote-sensing data with the global cylindrical equal-area projection and snow-depth data recorded at the China national meteorological stations, the Chang algorithm is modified and validated using meteorological observation data considering the influences from vegetation, wet snow, precipitation, cold desert, and frozen ground; the modified algorithm is dynamically adjusted based on the seasonal variation of grain size and snow density; the algorithm suitable for snow-depth retrieval in China covering Qinghai-Tibetan Plateau is done and the gridded daily snow depths are derived (Che et al, 2008). Based on the observed snow data from 74 weather stations, Wang et al (2013) have analyzed the accuracy of the snow data derived by Che et al (2008) in Qinghai-Tibetan Plateau.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ Figure 4] 20 VIC simulated snow cover was compared with snow depth derived from passive microwave remote-sensing data by Che et al (2008) and Dai et al (2015). Figure 5 shows the spatial distribution of observed and simulated daily average snow depths during evaluation.…”
Section: Hydrological Model Performance 15mentioning
confidence: 99%